Efektivitas Pembelajaran Pendidikan Pancasila pada Jam Terakhir terhadap Kedisiplinan Belajar Siswa SMK Negeri 2 Probolinggo - Ajeng Setyo Rini; Maharani Hidayah; Septa Rima Indarwanto; Muhammad Mujtaba Habibi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research was motivated by evaluating the effectiveness of Pancasila education learning in the last hour, considering that at this time students often experience a decrease in concentration and energy. The aim of this research is to evaluate the effectiveness of the allocation of Pancasila education learning time in the last hour on the discipline of students at SMK Negeri 2 Probolinggo. The method used in this research is descriptive qualitative research with questionnaires, observation and documentation. The research samples were students of class X TPM 1, X TPM 4, . The results of the questionnaire also show that learning Pancasila Education is categorized as "effective" because Pancasila Education has basic values ​​that emphasize discipline, responsibility and compliance with rules, and is able to shape students' character. Through this learning, students are not only given an understanding of the material but also how to apply Pancasila values ​​in shaping student character. This subject can also be an alternative "tool" to maintain student learning discipline.